Renewable energy in international business - Valtteri Kaartemo; Maria Alejandra Gonzalez Perez (Emerald, 2022)
Purpose: The guest editorial introduces the special issue entitled “Renewable energy in international business”
Design/methodology/approach: The paper presents a research agenda for the topic of the special issue and provides an overview of the articles included.
Findings: The guest editorial contains a discussion of the themes related to the topic, with a particular focus on the global production and adoption of renewable energies and dark sides of international renewable energy.
Research limitations/implications: The guest editorial considers how the articles included in the special issue contribute to research on renewable energy in international business and provides an avenue for future studies for a broader impact.
Originality/value: The discussion raises two important research streams that have remained overlooked in international business research, namely global production and adoption of renewable energies and dark sides of international renewable energy. The guest editorial also highlights the potential of international business research to become more relevant by incorporating conceptual, methodological and empirical insights that inform the multidisciplinary community of renewable energy researchers.